Dynamic setpoint calculation including collection and comfort requirements: Energy impact for museums in Southern Europe. (October 2017) - Kramer, Rick; van Schijndel, Jos; Schellen, Henk
Abstract: Firstly, this study presents an algorithm for setpoint calculation of museums' indoor temperature ( T ) and relative humidity ( RH ) integrating collection requirements according to ASHRAE and thermal comfort requirements according to adaptive temperature limits that follow from a one-year long comfort study in case study museum Hermitage Amsterdam. Secondly, this algorithm is implemented into a building energy simulation model to assess the energy impact for various cases: Five levels of museum indoor climate conditioning are applied to four building quality levels (ranging from a historical building to a purpose-built museum building) using weather data from six locations in Southern Europe. A validated building energy simulation model of museum Hermitage Amsterdam was adjusted to represent the four building quality levels, and technical-reference-year (TRY) weather data of six locations were used. The conclusions: The algorithm enables smooth control of hourly and seasonal adjustments in T and RH setpoints; the algorithm boosts energy efficiency due to more effective use of the permissible ranges of T and RH ; improving the building quality quickly follows the law of diminishing returns due to internal heat and moisture loads; supposing to result in the same collection risk, subclass As (with seasonal adjustments, but smaller hourly fluctuations) is more energy efficient than subclass Ad (no seasonal adjustments, but larger hourly fluctuations) for most locations.